PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN KOMUNIKASI INTERPERSONAL TERHADAP KOMITMEN ORGANISASI GURU DI SEKOLAH DASAR NEGERI GUGUS III UPTD PENDIDIKAN KECAMATAN RUMBAI KOTA PEKANBARU - Andri Saputra; M. Nur Mustafa; Mahdum Mahdum (Jurnal JUMPED (Jurnal Manajemen Pendidikan), 2017)
This research aimed to find out the influence of (1) the leadership style towardsteacher organizational commitment, (2) to find out the influence interpersonal communicationtowards teacher organizational commitment, (3) to find out the influence of both the leadershipstyle and interpersonal communication towards teacher organizational commitment. The sampleof the research was elementary school teachers in gugus III UPTD education Rumbai Districttotalling 105 teachers by using proportional random sampling technique. The data were collectedby distributing a set of questionnaire and were analyzed by using descriptive analysis, inferentialstatistics. The instrument reliability coefficient was counted through alpha cronbach formula.The findings of the research showed that partially, there was a positive influence of leadershipstyle towards teacher organizational commitment of 0,607, and there was a positive influenceof interpersonal communication towards teacher organizational commitment of 0,730 and therewas a positive influence of both the leadership style and interpersonal communication towardsteacher organizational commitment of 0,730.